2018
DOI: 10.1590/s0102-053620180219
|View full text |Cite
|
Sign up to set email alerts
|

Yield and composition of lavender essential oil grown in substrate

Abstract: The objective of this research was to evaluate the effect of successive harvesting times and shading on the production of biomass, yield and phytochemical composition of essential oil in leaves and inflorescences of soilless grown Lavandula dentata. Plants were grown in pots filled with sand, inside a polyethylene greenhouse, in a closed system at UFSM. Plants were harvested at 150, 213 and 320 days after planting date (DAP) in winter, spring and summer, respectively. At 150 DAP, a 50% shading screen was insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In the present study the essential oil (OE) content vegetable biomass ratio was 0.75. In another study, Mambri (2018) data showed out of the parts of the plant used in the extraction, the one third section of the apical aerial part produced the most OE when it was in full bloom (Mambri, 2018). Overall, the OE values suggested that L. dentata produced high levels of OE and the values recorded in this study were much higher than those efficiency of 0.56 and 0.40 for essential oils from leaves and flowers obtained by Martins, Gomes, Malpass and Okura (2019).…”
Section: Results and Discusionmentioning
confidence: 42%
See 1 more Smart Citation
“…In the present study the essential oil (OE) content vegetable biomass ratio was 0.75. In another study, Mambri (2018) data showed out of the parts of the plant used in the extraction, the one third section of the apical aerial part produced the most OE when it was in full bloom (Mambri, 2018). Overall, the OE values suggested that L. dentata produced high levels of OE and the values recorded in this study were much higher than those efficiency of 0.56 and 0.40 for essential oils from leaves and flowers obtained by Martins, Gomes, Malpass and Okura (2019).…”
Section: Results and Discusionmentioning
confidence: 42%
“…These morphological structures have biological properties with specific ecological functions. This variation in morphological characters and volatile constituents may be caused by plant interactions with environmental abiotic factors (Gonçalves & Romano, 2013;Mambri, 2018). In addition genetic factors are known to influence the yield and chemical composition of the essential oil (Morais, 2009) and may vary within the same species (Properzi, Angelini, Bertuzzi, & Venanzoni, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results obtained, slight variations are observed in the chemical composition of the A. pyrethrum essential oil collected from different regions. These differences can be explained by factors such as soil and weather conditions, also the extraction method and the drying of the material previous extraction [29][30][31][32][33][34][35] . However, spathulenol and germacrene D are compounds known for their insecticidal activity; which makes the essential oil of A. pyrethrum an excellent natural insecticide.…”
Section: According To the Results Of Gc-ms Analysis Ofmentioning
confidence: 99%
“…On the other hand, high concentrations of 1,8 cineole, camphor, or terpinen-4-ol adversely affect the quality of this oil (Góra and Lis, 1995). Compost application in growing basil contributes not only to an increase in essential oil content but also increases the concentration of linalool and borneol in the oil, with a simultaneous decrease in the content of methyl chavicol and 1,8-cineole (Taie et al, 2010 andMambrí et al, 2018).…”
Section: Effect Of Organic and Biofertilizers On Lavender Essential Oils Compositionmentioning
confidence: 99%
“…Lavender is characterized by its high-quality essential oil which is considered raw material for many industries such as perfumes, cosmetics, and pharmaceutical industries (Chrysargyris et al, 2020;Silva et al, 2017;González-Coloma et al, 2011;Touati et al, 2011). Lavender herbage is rich in its oil content which has a high number of essential oils such as1,8 cineole, camphor, borneol, fenchol, α-pinene, β-pinene, trans-pinocarveol, and linalool (Mambrí et al, 2018). According to (Demissie et al, 2011;Meftahizade et al, 2011) which reported the antiseptic activity of lavender plants, lavender essential oils were traditionally used as an agent in swabbing of wounds, burns, insect bites, and in veterinary practice to kill parasites.…”
Section: Introductionmentioning
confidence: 99%